2018
DOI: 10.1002/mrm.27388
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic per slice shimming for simultaneous brain and spinal cord fMRI

Abstract: Purpose Simultaneous brain and spinal cord functional MRI is emerging as a new tool to study the central nervous system but is challenging. Poor B0 homogeneity and small size of the spinal cord are principal obstacles to this nascent technology. Here we extend a dynamic shimming approach, first posed by Finsterbusch, by shimming per slice for both the brain and spinal cord. Methods We shim dynamically by a simple and fast optimization of linear field gradients and frequency offset separately for each slice in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 49 publications
0
73
0
Order By: Relevance
“…We plan to use the current dataset to systematically investigate the preprocessing and analysis steps to increase the sensitivity and specificity of spinal cord fMRI to detect sensory activity. Recently, methods for simultaneous functional imaging of the spinal cord and brain in humans have been developed ( Finsterbusch et al, 2013 ; Islam et al, 2019 ; Vahdat et al, 2015 ). Considering the somatotopic organization of sensory processing in the brain, simultaneous spinal cord-brain fMRI may further improve our ability to differentiate sensory activity between stimulation sites ( Grodd et al, 2001 ; Penfield and Boldrey, 1937 ; Qi and Kaas, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…We plan to use the current dataset to systematically investigate the preprocessing and analysis steps to increase the sensitivity and specificity of spinal cord fMRI to detect sensory activity. Recently, methods for simultaneous functional imaging of the spinal cord and brain in humans have been developed ( Finsterbusch et al, 2013 ; Islam et al, 2019 ; Vahdat et al, 2015 ). Considering the somatotopic organization of sensory processing in the brain, simultaneous spinal cord-brain fMRI may further improve our ability to differentiate sensory activity between stimulation sites ( Grodd et al, 2001 ; Penfield and Boldrey, 1937 ; Qi and Kaas, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regions of high susceptibility like tissue/air interfaces or metal implants will produce significant field inhomogeneities and may require effective shimming including active shims with high current capacities and higher order terms at high field strengths 55 . Dynamic shimming (e.g., Siemens BioMatrix CoilShim and Slice Adjust) now permits localized shimming based on slice or voxel 56,57 . The aim of dynamic shimming is to address inhomogeneities over single slices or regions that cannot be adequately minimized by conventional field shimming 58 .…”
Section: Discussionmentioning
confidence: 99%
“…55 Dynamic shimming (e.g., Siemens BioMatrix CoilShim and Slice Adjust) now permits localized shimming based on slice or voxel. 56,57 The aim of dynamic shimming is to address inhomogeneities over single slices or regions that cannot be adequately minimized by conventional field shimming. 58 Dynamic shimming can be challenging because of the settling times that may be required after changing the shim value.…”
Section: D B 0 Field Homogeneity and Rtmentioning
confidence: 99%
“…In fact, Ozturk et al showed that T 2 *‐weighted gradient‐echo scans in the spinal cord show multiple sclerosis lesions with greater regularity compared with conventional T2‐weighted spin echo imaging . With growing interest in spinal cord functional MRI, there is also an increasing need to measure T 2 * relaxation times in healthy volunteers to carefully design more sensitive sequences for gradient‐echo‐based functional spinal cord imaging. It should also be noted that conventional, longer echo T2‐weighted imaging of the spinal cord does not demonstrate gray matter (GM)/white matter (WM) contrast to the extent that T 2 *‐weighted gradient‐echo scans do, which, if optimized for contrast, can offer a unique ability to measure both WM and GM atrophy in disease.…”
Section: Introductionmentioning
confidence: 99%